The association between athletic training time and the sagittal curvature of the immature spine - Wojtys, E. M.; Ashton-Miller, J. A.; Huston, L. J.; Moga, P. J. (The American Journal of Sports Medicine, 2000)
Strenuous physical activity is known to cause structural abnormalities in the immature vertebral body. Concern that exposure to years of intense athletic training may increase the risk for developing adolescent hyperkyphosis in certain sports, as well as the known association between hyperkyphosis and adult-onset back pain, led us to examine the association between cumulative hours of athletic training and the magnitude of the sagittal curvature of the immature spine. A sample of 2,270 children (407 girls and 1,863 boys) between 8 and 18 years of age were studied. An optical raster-stereographic method was used to measure the mid-sagittal curvatures of the surface of the back while the subject was in the upright standing position to quantify the angles of thoracic kyphosis and lumbar lordosis. These data were then correlated with self-reported hours of training measured by interview and questionnaire. The possible effects of age, sex, sport, and upper and lower body weight training were investigated. The results in these young athletes showed that larger angles of thoracic kyphosis and lumbar lordosis were associated with greater cumulative training time. Gymnasts showed the largest curves. Lack of sports participation, on the other hand, was associated with the smallest curves. Age and sex did not appear to affect the degree of curvature.